Beyond focal cortical lesions in MS: An in vivo quantitative and spatial imaging study at 7T. (10th November 2015) - Louapre, Céline; Govindarajan, Sindhuja T.; Giannì, Costanza; Langkammer, Christian; Sloane, Jacob A.; Kinkel, Revere P.; Mainero, Caterina
Abstract : Objectives: Using quantitative T2* 7-tesla (7T) MRI as a marker of demyelination and iron loss, we investigated, in patients with relapsing-remitting multiple sclerosis (RRMS) and secondary progressive multiple sclerosis (SPMS), spatial and tissue intrinsic characteristics of cortical lesion(s) (CL) types, and structural integrity of perilesional normal-appearing cortical gray matter (NACGM) as a function of distance from lesions. Methods: Patients with MS (18 RRMS, 11 SPMS), showing at least 2 CL, underwent 7T T2* imaging to obtain (1) magnitude images for segmenting focal intracortical lesion(s) (ICL) and leukocortical lesion(s) (LCL), and (2) cortical T2* maps. Anatomical scans were collected at 3T for cortical surface reconstruction using FreeSurfer. Seventeen age-matched healthy participants served as controls. Results: ICL were predominantly located in sulci of frontal, parietal, and cingulate cortex; LCL distribution was more random. In MS, T2* was higher in both ICL and LCL, indicating myelin and iron loss, than in NACGM ( p < 0.00003) irrespective of CL subtype and MS phenotype. T2* was increased in perilesional cortex, tapering away from CL toward NACGM, the wider changes being for LCL in SPMS. NACGM T2* was higher in SPMS relative to RRMS ( p = 0.006) and healthy cortex ( p = 0.02). Conclusions: CL had the same degree of demyelination and iron loss regardless of lesion subtype and disease stage. Cortical damage expanded beyond visible CL, close to lesions in RRMS, and more diffusely in SPMS. Evaluation of NACGM integrity, beyond focal CL, could represent a surrogate marker of MS progression.